Uso de lidocaína alcalinizada na insuflação do balonete do tubo endotraqueal em pacientes submetidos a cirurgia de tireoidectomia: ensaio clínico randomizado - BARBOSA JUNIOR, Gaudencio (2023)
Introduction: Thyroidectomy is indicated for malignant, or suspicious, and benign lesions, in the presence of obstructive, aesthetic symptoms and hyperthyroidism. The procedure requires orotracheal intubation to maintain life, where the patient is subject to effects such as coughing and swelling. Lidocaine used to inflate the endotracheal cuff has been shown to be an important mechanism for preventing these effects. Objective: To compare the postoperative effects of endotracheal tube cuff inflation with alkalized lidocaine after general anesthesia in patients undergoing thyroidectomy surgery. Methods: This is a randomized, double-blind clinical trial, carried out between August 2020 and August 2022 at Hospital São Domingos, São Luís - MA. patients were drawn with numbers from 1 to 100, being divided into the control group (G1), in which the cuff was filled with 0.9% saline solution, and in the intervention group (GLA), in which the cuff was filled with lidocaine 2% and 8.4% sodium bicarbonate. Results: Predominantly women aged between 41 and 50 years were observed. Most are residents of the state capital, are brown, married, with individuals with complete secondary education being the most observed in the CG and in the GLA, complete higher education. After extubation, the CG had significantly higher medians (p = 0.033) for SBP (124 mmHg) than the GLA (124 mmHg), as well as for the HR (median GC = 86 bpm; median GLA = 80 bpm), p = 0.034. DBP and MAP presented medians in the total population of, respectively, 75.5 mmHg, 98 mmHg (p < 0.05). The CG had a greater number of individuals with phonation sustaining capacity in 2h (88.0%) than the GLA (82.0%), the latter showed a significant increase (p value = 0.031) in the 24h postoperative period (94.0%) in relation to 2h. The GLA had a higher percentage of individuals with Foreign Body Sensation (58.0%) than the CG (52.0%), which showed a significant reduction (p = 0.039) in 24h (36.0%). Conclusions: There was no protective effect of the use of alkalized Lidocaine on swallowing sensation and complaints after thyroidectomy surgery. However, in the hemodynamic response, there was a significant improvement in the intervention group after extubation.